"Cotidiano de vida y salud en un colectivo de personas con discapacidad física en la asociación Fe Divina de la ciudad de Huamachuco" - Fernandez Armas, Martha Soledad (2010)
The intention of the present study the phenomenon belonged develar vivenciado to the persons with physical disability, seeking to understand (include) in its entirety deep the essence of the phenomenon by means of an attitude dialógica that allowed to know the experiences of the group in study. This qualitative study of path phenomenology is based on some concepts of Husserl's philosophy. The question orientadora was which is the daily one of life and health in a group of persons with physical disability in the association Divine Faith of Huamachuco's city 2009?. The subjects of the investigation were 8, in adult age. The descriptions were obtained across engraved interviews, which were realized in the domiciles of every subject of investigation. The information was registered for his (her, your) careful analysis, obtaining essential aspects of the phenomena. Pictures were elaborated by the units of meaning obtained, by his(her, your) respective reduction phenomenology, pictures of convergence, ideographical analysis and nomotético; there being obtained 74 units of meaning, which qualify in 16 categories, Confronting my disability, impotence, rejection and nonchalance of the society, being disabled, living in the association, I feel happy mobilizing me, companionship and friendship, I have the support of my family, daily of work, worry for his(her, your) health, Fe and confidence in God, longing for loving and for being loved, equality of opportunities, fulfilling my duties and rights, need of support, free profitable time. The analysis phenomenology demonstrates that the persons with physical disability we need to be accepted and not rejected by the society.